Kesesuaian Kompetensi Lulusan SMK dengan Kebutuhan Dunia Usaha dan Industri - Hidayati, Arina; Barr, Farah Dzil; Sigit, Kharisma Nawang (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2021)
This research is intended to find out the relevance of Vocational High School graduates’ competency to business and industrial worlds’ need. In this study, the author wants to obtain data in-depth through qualitative research method with case study strategy. Techniques of collecting data taken were interview, observation, and documentations study. To find out data reliability and validity, the author chose data, source, and time triangulations as data validating instrument. Technique of analyzing data used was Spradley’s domain analysis. The results of research obtained are, among others, as follows. The compatibility of SMK N 1 Batang graduates’ competency in accounting specialty to the Business/Industrial World’s need. The SMK N 1 Batang graduates in Accounting specialty, viewed from the curriculum taught, have been compatible to the Business/Industrial World’ need. However, viewed from standard competency used by SMK is still different from that used by Business/Industrial World. This difference makes not all graduates of SMK N 1 Batang capable of working corresponding to their specialty.